The Analysis Study of Interventions of Dry Eye: A Comprehensive Systematic Review - Iffan Soffyan Ismail; Yuce Yuanita (International Medical Journal Corp. Ltd, 2024)
Introduction : Dry eye disease (DED) is a common, multifactorial condition affecting the tear film and ocular surface, leading to discomfort, visual disturbances, and progressive ocular damage if untreated. DED involves a complex interplay among anatomical structures, inflammatory pathways, and environmental factors. It is classified into aqueous-deficient and evaporative types, often presenting as mixed forms. DED significantly affects quality of life, daily functionality, and psychological well-being. This systematic review synthesizes current evidence on DED pathophysiology, classification, diagnosis, and management while highlighting recent advancements in therapeutic strategies. Methods :This review adhered to PRISMA 2020 guidelines, focusing on original research published since 2018. Inclusion criteria targeted studies on DED’s inflammatory mechanisms, diagnostic tools, and treatment approaches. Databases searched included PubMed, ScienceDirect, Embase, Cochrane Library, and Web of Science. Keywords such as “dry eye disease,” “ocular surface inflammation,” and “meibomian gland dysfunction” were employed. Following a rigorous screening process, eight studies met the inclusion criteria for comprehensive analysis. Results : The analysis reaffirmed the central role of inflammation in DED pathophysiology, driven by cytokines and matrix metalloproteinases. Emerging diagnostics, such as tear osmolarity tests and meibography, enhance disease identification. Treatment advancements emphasize anti-inflammatory therapies, artificial tears, and meibomian gland support. The review highlights the burden of DED on quality of life and identifies gaps in addressing work-related and environmental stressors. Conclusion : DED is a complex disorder requiring a multidisciplinary approach. Future research should prioritize innovative therapies targeting underlying mechanisms, comprehensive patient education, and integration of mental health support. Holistic management can mitigate the burden of DED and improve patient outcomes.